Isolation and characterization of Priestia megaterium KD7 for the biological control of pear fire blight - Cui, Zeling; Hu, Lina; Zeng, Linglu; Meng, Wanqiu; Guo, Dong; Sun, Li (Frontiers in Microbiology, 2023)
Erwinia amylovora is a plant pathogen that causes fire blight disease in Rosaceous plants, such as pear and apple. To develop an effective biocontrol method to suppress E. amylovora, a total of 16 bacteria were isolated from pear orchard soil in China and screened for antagonistic activity in vitro. Among them, 9 isolates that exhibited antagonistic activity against E. amylovora were identified, including Bacillus atrophaeus, Priestia megaterium (previously known as Bacillus megaterium) and Serratia marcescens based on the partial 16S rDNA sequence analysis and similarity search. The plate confrontation experiments showed that strain 8 (Priestia megaterium strain KD7) had strong antagonistic activity against E. amylovora. The methanolic extract from cell-free supernatant of strain KD7 displayed high antibacterial activities against E. amylovora. Furthermore, the active compounds of strain KD7 were separated by thin layer chromatography (TLC) and the amino acids were detected by the presence of a spot with retention factor (Rf) of 0.71. Next, three lipopeptides were identified with high-resolution mass spectrometry (HRMS), including C13-surfactin, C15-surfactin and C14-iturin A. Strain KD7 showed multiple antibiotic resistance, such as ampicillin, erythromycin, penicillin and tetracycline. The detached pear leaves, twigs and fruits assay showed that both protective and curative action with strain KD7 had the ability to decrease the development of fire blight. Taken together, P. megaterium strain KD7 is a potential effective biocontrol agent against fire blight.